2022
DOI: 10.1172/jci160186
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting DNA methylation improves antitumor immunity in ovarian cancer

Abstract: Cancer cells resist the immune response in a process known as immune editing or immune evasion. Therapies that target the immune system have revolutionized cancer treatment; however, immunotherapies have been ineffective for the majority of ovarian cancer cases. In this issue of the JCI , Chen, Xie, et al. hypothesized that hypomethylating agent (HMA) treatment would induce antitumor immunity to sensitize patients with ovarian cancer to anti-PD-1 immunotherapy. The authors performed a ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“… 75 Specifically, B cells and tertiary lymphoid structures in the TME may predict a response to immune checkpoint blockade. 34 Additionally, B cells can also play immunosuppressive roles in autoimmune diseases 76 and cancer. 77 These immunosuppressive B cells are called B regulatory cells (B regs ), and they are known to produce IL-10, which is a cytokine that suppresses T cells and the T helper 1 immune response.…”
Section: Resultsmentioning
confidence: 99%
“… 75 Specifically, B cells and tertiary lymphoid structures in the TME may predict a response to immune checkpoint blockade. 34 Additionally, B cells can also play immunosuppressive roles in autoimmune diseases 76 and cancer. 77 These immunosuppressive B cells are called B regulatory cells (B regs ), and they are known to produce IL-10, which is a cytokine that suppresses T cells and the T helper 1 immune response.…”
Section: Resultsmentioning
confidence: 99%
“…The forest map showed that the feature score (HR = 1.69, 95% CI = 1.17–2.45, p = 0.006), the TNM staging system, and tumor recurrence (HR = 2.58, 95% CI = 1.79–3.72, p < 0.0001) were independent prognostic factors for LUAD, while smoking history and tumor subtype were not ( Figure 5E ). DNA methylation is closely related to tumor immune microenvironment ( Chiappinelli and Baylin, 2022 ; Li et al, 2022 ). We investigated the relationship between methylation feature scores and tumor immune infiltration.…”
Section: Resultsmentioning
confidence: 99%
“…DNA methyltransferase inhibitors (DNMTis), which are epigenetic modulators, have been shown to induce the cytoplasmic sensing double-stranded RNA (dsRNA) antiviral pathway, upregulate type I IFN (Chiappinelli et al, 2015), activate CD8 T-cell, increase the number of immune cells (Wright et al, 2016;Stone et al, 2017;Vergote et al, 2018), and synergistically downregulate programmed death ligands (PD-L1 and PD-L2) with ICIs to exert antitumor effects. In patients with recurrent chemoresistant OC, hypomethylating agents (HMAs) in combination with ICIs to increase immune signaling and improve the response to immune checkpoint blockade in OC also appear to be a viable therapeutic strategy (Chiappinelli et al, 2022). A phase II clinical trial including 35 patients with platinum-resistant OC (NCT02901899) combined guadecitabine, a secondgeneration HMA, with pembrolizumab, an inhibitor of PD-1 and found that 34% of patients obtained clinical benefit (Chiappinelli et al, 2015).…”
Section: Discussionmentioning
confidence: 99%